Prototipe Notifikasi Banjir Berbasis IoT - Muh Sabran M, Andi; Suwardoyo, Untung (Jurnal Sintaks Logika, 2024)
The lack of initial flood risk mitigation information to the community causes a lot of property damage and loss of life. This research aims to design a flood notification prototype so that people can avoid flood disasters. This research uses quantitative methods with an experimental approach, utilizing an ESP 8266 microcontroller connected to a wireless network and ultrasonic sensors to detect water levels based on the Internet of Things (IoT). This research succeeded in designing a flood notification system to make it easier for the public to obtain real-time water level information as an initial stage of early evacuation.